Creating Authentic Assessment Tools for Independent Learning in Islamic Boarding Schools - Zuniati, Mai; Wawan, Wawan; Anggraini, Dian; Irmawati, Irmawati; Fatimah, Dwi Nur; Sugilar, Hamdan; Mispani, Mispani; Setiawan, Agus; Dimyati, Moh. (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
This study aims to develop authentic assessment tools oriented to Independent Learning for Islamic boarding schools in the PCLP Ma'arif NU Metro environment. Through this approach, teachers will receive intensive assistance in designing assessment tools relevant to Islamic boarding schools' educational needs. This activity also aims to strengthen the cooperative relationship between Ma'arif University Lampung and various schools in Lampung Province, so that a positive synergy is created that supports improving the quality of education. The process of developing this assessment tool will involve a series of workshops and training designed to equip teachers with the skills and knowledge needed. Evaluation of the success of the program will be carried out through analysis of the results of the assessment tool design made by participants and feedback given during and after the workshop activities. The expected results of this community service program include: 1) Teachers can design authentic assessment tools oriented to Independent Learning; 2) Closer cooperation between Ma'arif University Lampung and schools in the region; and 3) Scientific publications in the form of PKM books with ISBN or articles in community service journals. It is hoped that this activity will not only provide a real contribution to improving the quality of education in Islamic boarding school-based schools but also support the achievement of the Independent Learning goal. With the existence of authentic and relevant assessment tools, it is hoped that the learning process in Islamic boarding schools will be more effective and by the demands of the times. In addition, synergy between higher education institutions and schools in the region will strengthen an inclusive and sustainable education ecosystem.